The role of periooperative rehabilitation in patients with abdominal aortic aneurysm in the opinion of medical - Maniak, Diana Karolina; Rożniecka-Hełmińska, Adrianna; Kupcewicz, Ewa (Journal of Education, Health and Sport, 2018)
Introduction: Abdominal aortic aneurysm is an increasingly common anomaly. As a result of the development of medicine, the number of previously diagnosed aortic aneurysms increases, which corresponds to increased survival of patients with this disease. In connection with the above, the number of patients requiring treatment of this disease increases, and thus the implementation of rehabilitation perioperative procedures. Aim of the study: Analysis of the opinion of medical personnel on the role of perioperative rehabilitation in patients undergoing abdominal aortic aneurysm surgery and the indication of priorities in the procedure. Materials and methods: The study was conducted using the diagnostic survey method using the original questionnaire. The study involved 102 people, including 76 male nurses (74,50%) and 26 doctors (24,49%) with an average age of 37.3 (± 9.4) years. The questionnaire contained questions in which the staff expressed their opinion on the role of perioperative rehabilitation in patients undergoing surgery for abdominal aortic aneurysm. The obtained data was subjected to statistical analysis, in which p <0.05 was assumed as the level of significance. Results: Both groups, nurses and doctors, gave similar answers to the majority from asked questions. However, as a result of the analysis, discrepancies in opinion were noticed. It was found that nurses (82.89%) more often expressed their opinion on the implementation of rehabilitation in the pre-operative period, while doctors more often (15.38%) gave a negative answer. Nurses statistically more often (78.95%) than doctors (50.00%) considered the exercises to deal with the surgical wound to be the most important. Nursing staff statistically more often (59.21%) than doctors (26.92%) pointed to the need to continue rehabilitation in the outpatient period. Conclusions: Perioperative rehabilitation carried out in patients after TAB is an important element of treatment. It should be implemented already before the operation and continued at the outpatient stage, when the patient leaves the hospital. Employment at full-time physical therapist wards would facilitate the implementation of a comprehensive rehabilitation process and the significance would shorten the period of patient recovery after surgery.